CDC27-ODC1 Axis Promotes Metastasis, Accelerates Ferroptosis and Predicts Poor Prognosis in Neuroblastoma - Qiu, Lin; Zhou, Rui; Luo, Ziyan; Wu, Jiangxue; Jiang, Hua (Frontiers in Oncology, 2022)
Neuroblastoma (NB) is a devastating malignancy threatening children’s health, and amplification of the MYCN associated with treatment failure and a poor outcome. Here we report cell division cycle 27 (CDC27), an important core subunit of anaphase promoting complex, predicted a poor prognosis of NB patients. In functional assays, we demonstrated CDC27 promoted cell growth, metastasis and sphere-formation ability of NB cells both in vitro and in vivo. For further understanding the potential mechanism, RNA-sequencing was applied, and results revealed that downregulation of CDC27 led to markedly reduced expression of ODC1, which is a well-established direct target of MYCN. Subsequently, we further illustrated suppression of ODC1 significantly attenuated the promotion effect of CDC27 on proliferation, metastasis, sphere-formation ability of NB cells, hinting that CDC27 exerted its biological behavior in NB at least in part in an ODC1-dependent manner. Besides, CDC27 also rendered cells more vulnerable to ferroptosis, while knockdown of ODC1 remarkably inversed the pro-ferroptosis effect of CDC27. Collectively, our data first reported CDC27/ODC1 axis promoted tumorigenesis and acted as a positive regulator of ferroptosis in NB, highlighting CDC27 may represents a novel therapeutic strategy and prognostic biomarker in neuroblastoma.